Analysis of Synoptic Disturbance in Maritim Continent Using Spherical Harmonics Transformation Method - Sayful Amri; Faiz Rohman Fajary; Tri Wahyu Hadi (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2020)
This study aims to modify the idea of ​​WK99-analyzing the existence of signature in wave-number and frequency spectrum when the analyzed Outgoing Longwave Radiation (OLR) data is associated with a unique phenomenon in Maritime Continent (MC), Borneo vortex (BV). Although BV is often related to easterly equatorial wave disturbances, there was no specific study to examine its behavior in the spectral domain. The purpose of this study is to develop a method to diagnose certain signatures of BV through spectrum analysis of OLR data when BV occurs. In contrast to previous studies, to present the unique phenomenon in MC as a target for diagnostics, spectrum analysis is performed by Spherical Harmonics (SH). The results of the OLR data spectrum comparison when BV occurs with the OLR data spectrum when BV does not occur that in the anti-symmetrical component when BV occurs, the tropical depression-mixed Rossby gravity (TD-MRG) wave spectrum is stronger, especially in zonal wave-numbers 5 to 10 and frequencies 0.12 to 0.2. Similar to the anti-symmetrical component, the TD-MRG spectrum of the symmetrical component is also stronger at zonal wave-numbers 5 to 10 and frequencies 0.12 to 0.2. Moreover, the westward-propagating inertio-gravity (WIG) wave spectrum in the symmetrical component is also stronger at the time of BV than when there is no BV, especially at zonal wave-numbers 7 to 13 and frequencies 0.38 to 0.5. It can be concluded that when BV occurs, equatorial waves that propagate to the west, especially the types of TD-MRG and WIG waves are stronger than when BV did not occur. The results of durational grouped spectrum analysis of OLR data when BV occurs indicate that the longer the duration of BV occurs, the stronger the spectrum of TD-MRG and WIG wave types gets.